A practical guide to identifying members of the Bemisia tabaci species complex: and other morphologically identical species - Boykin, Laura M.; De Barro, Paul J. (Frontiers in Ecology and Evolution, 2014)
Members of the Bemisia tabaci species complex (whiteflies) are a considerable threat to a broad range of agriculture and horticulture food and fiber crops. There are hundreds of papers a year published on the members of B. tabaci species complex, many failing to either correctly identify the species involved or confusing identity. Correct identification is a crucial first step in any study, yet all too often, especially in cases where the primary focus of the study is plant pathology, is overlooked. The whitefly research community has struggled for years with common terminology and consistent methods for species identification of various members of the complex due to 1) the lack of a reliable global genetic resource and 2) the complexities of the phylogenetic methods needed to identify unknown individuals correctly. The goal of this paper are to provide a practical guide for identifying unknown whiteflies using a global curated dataset of mitochondrial COI that is freely available at http://dx.doi.org/10.4225/08/50EB54B6F1042. The methods and resources outlined here can be readily extended to other species that are morphologically indistinguishable.